Water and sediment quality of murum reservoir, inundated plieran river and danum river - Toh, Yu Mei (Universiti Malaysia Sarawak (UNIMAS), 2015)
Dam construction could lead to environmental problems. Three stations, inundated Pleiran River (S1), inundated Danum River (S2) and Murum reservoir (S3) were selected to determine the water quality at 3 depths and sediment quality. Samples collection were in July 2014 and February 2015. S1 which was near to the submerged vegetation area showed the highest BOD5 (6.77 mg/L), the highest COD (122.03 mg/L) and the highest chl-a (12.13 mg/m3) at subsurface in July 2014. S1 had the highest turbidity (50.70 NTU), the highest TAN (0.791 mg/L), the highest SRP (39.09 μg/L) and the highest TS2- (0.09 mg/L) at 20 m depth in February 2015. Total sulfide in both trips showed similar trend at 3 depths. Both sediment texture in S1 and S3 were sandy clay loam; S2 was clay. TSI showed all stations were eutrophic. S2 and S3 at subsurface in July 2014 and S1 and S3 at subsurface in February 2015 showed WQI of Class II (76.5 – 92.7). Other stations fall in Class III (51.9 – 76.5) and IV (31.0 – 51.9) which could affect the healthy growth of aquatic life. Therefore, it is recommended to pre-clear vegetation before the impoundment of the river.